Semiotic Analysis of Sign Language Used by Elisa ‎in the Shape of Water Movie - Aqilah, Zalfa; Halim, Abd; Nur, Sahril (IAIN KENDARI, 2024)
This research analyzes the use of sign language used by a mute adult woman named Elisa based on ‎the movie The Shape of Water. In this research, the researcher focuses on the features of sign ‎language used by Elisa to communicate with people in the movie. In addition, the researcher also ‎used a qualitative approach and content analysis design. Where, this research collected, organized, ‎and described the features of sign language based on the movie The Shape of Water. The main aim ‎of this research is to find out more about the features of sign language and the usage of sign ‎language found in The Shape of Water movie. The result of this research found several sign ‎language features used by Elisa to help her communicate, such as finger spelling, spatial grammar ‎and simultaneity, placement, non-manual feature and handling, of these features, the most dominant ‎feature used by Elisa is the non-manual feature